Identification and Characterization of Pathogenic Enterobacterial Isolates Responsible for Egg Contamination - Jain , Ashish Kr.; Yadav, Rajesh (International Journal of Poultry Science, 2016)
This study aims at the isolation and identification of pathogenic enterobacteria responsible for egg contamination in poultry farms by using different biochemical tests and molecular characterization i.e. 16s rRNA gene analysis. A total of 90 eggs were collected from three different Poultry farms in Jaipur city, India. Micro-organisms were isolated by using differential medium i.e. MacConkey agar, EMB agar and characterized by using different biochemical tests like catalase test, indole test, methyl-red and voges-proskauer test (MR-VP), citrate utilization test, H2S production, Urease test, Gas production, Glucose and Lactose fermentation etc. On the basis of biochemical analysis selected isolates were subjected to 16s rRNA gene analysis, as 16s rRNA gene analysis is a powerful technique for bacterial taxonomy and identification. Both the biochemical and molecular analysis revealed that most of the isolates belong to family Enterobacteriaceae and were identified as Escherichia coli O157:H7str. EC4115, Staphylococcus epidermidis ATCC 14990 and Pluralibacter gergoviae. The study concludes that the eggs and egg products are contaminated with pathogenic microbes and may cause diseases if consumed raw or uncooked. Thus, there is a serious need to pay attention in increasing the hygienic level of commercial eggs so as to prevent the occurrence of prevalence of microbial contamination in eggs.